Exploring digital platforms, cultural tourism and online learning of museums worldwide - Zulkifli, Amirul Hafiz; Abu Bakar, Mohd Syuhaidi; Harun, Khairul Nishak; Mat Shuki, Mohd Syafiq (2020)
In recent years, the institution of the museum has changed its dominance to become increasingly focused on visitor attractions. The equivalent of 4.0 revolution museum institutions worldwide implemented a paradigm shift in demonstrated that it remains relevant for the eyes of the public (visitors). The displacement of the museum is strengthened as a digital platform, cultural tourism, and online learning for the global community. This study presents a conceptual framework of a museum which relevant to the community through three (3) aspects - digital platforms, cultural tourism, and online learning. This study focused on these three aspects that reflected the changes in the perspectives of professional museums rather than served as a traditional museum (focused on custodial care) to more current (focused to educate and entertain the community). This study confirms that a museum now connects with three aspects that associates with digital aspects, online learning aspects and cultural tourism aspects towards the community and tourists.